Measuring Systemic Risk on the Indonesia’s Banking System - Mansur, Alfan (Badan kebijakan Fiskal, 2018)
Inter-connectedness is one important aspect in measuring the degree of systemic risk arising in the banking system. In this paper, this aspect besides the degree of commonality and volatility are measured using Principal Component Analysis (PCA), dynamic Granger causality tests and a Markov regime switching model. These measures can be used as leading indicators to detect pressures in the financial system, in particular the banking system. There is evidence that the inter-connectedness level together with degree of commonality and volatility among banks escalate substantially during the financial distress. It implies that less systemically important banks could become more important in the financial system during the abnormal times. Therefore, the list of systemically important banks as regulated in the Law on Prevention and Mitigation of Financial System Crisis (UU PPKSK) should be updated more frequently during the period of financial distress.